2022
DOI: 10.3390/biology11020338
|View full text |Cite
|
Sign up to set email alerts
|

Acute Changes in Heart Rate Variability to Glucose and Fructose Supplementation in Healthy Individuals: A Double-Blind Randomized Crossover Placebo-Controlled Trial

Abstract: Background: It is unknown how different types of carbohydrates alter the cardio-autonomic system in healthy individuals. Therefore, the aim of this study was to investigate how heart-rate variability changes to single dose ingestion of glucose, fructose, glucose and fructose, and an artificial sweetener (sucralose). Methods: In a double-blind randomized crossover placebo-controlled setting, 15 participants received all study-specific substances in liquid form. During each 2-h visit, venous blood glucose was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…In addition, Tanaka et al (1999) provided restricted food access for 6 h during the lights-on (inactive) phase in nocturnal rats and found that the organisms became more active. It should be noted that a recent study showed that heart rate variability (HRV) and blood pressure (BP) are directly affected by changes in blood glucose levels which rise as a result of food intake, and that various types of carbohydrates affect heart rate differently, suggesting that acute changes in food intake affect physiology in humans ( Eckstein et al, 2022 ). There is also evidence in the literature suggesting acute meal-induced metabolic changes result in acute inflammatory responses in humans that may lead to an increased risk of chronic inflammatory diseases ( Mazidi et al, 2021 ).…”
Section: Exogenous Stimuli That Affect Masking Behaviormentioning
confidence: 99%
“…In addition, Tanaka et al (1999) provided restricted food access for 6 h during the lights-on (inactive) phase in nocturnal rats and found that the organisms became more active. It should be noted that a recent study showed that heart rate variability (HRV) and blood pressure (BP) are directly affected by changes in blood glucose levels which rise as a result of food intake, and that various types of carbohydrates affect heart rate differently, suggesting that acute changes in food intake affect physiology in humans ( Eckstein et al, 2022 ). There is also evidence in the literature suggesting acute meal-induced metabolic changes result in acute inflammatory responses in humans that may lead to an increased risk of chronic inflammatory diseases ( Mazidi et al, 2021 ).…”
Section: Exogenous Stimuli That Affect Masking Behaviormentioning
confidence: 99%
“…Unfortunately, our search for studies in human subjects was only able to identify controlled studies reporting the acute effects of acute fructose ingestion (several hours). In contrast, animal studies showing deleterious effects on hemodynamics have largely assessed the long-term effects (weeks to months) of fructose on blood pressure [ 44 , 45 , 46 , 47 ], with some animal studies using dietary amounts exceeding what is typically ingested by people [ 36 , 37 , 38 , 39 ]. We identified only a limited number of publications reporting the direct effects of fructose on blood pressure in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this, our study demonstrates clear evidence that pre-exercise CHO consumption, independent of composition, does not have an ergogenic effect on performance in high-intensity anaerobic endurance exercise and moderate resistance exercise. The metabolic responses at rest seen in this study following the consumption of CHO have previously been investigated by our research group [ 17 , 25 , 26 ]. On this basis, this study was conducted since the time until reaching peak blood glucose and peak lactate values are reached in healthy individuals roughly 30 min after consumption which could have had the implication of a higher performance in comparison to placebo.…”
Section: Discussionmentioning
confidence: 99%
“…However, for safety reasons and the level of experience of the participants, we were unable to increase the weights. Since the metabolic responses to the applied protocol at rest are well-researched, our findings may deliver valuable information for male and female athletes consuming CHO drinks regularly prior to exercise [ 17 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%